Transcriptome sequencing of sheep hypothalamic tissue reveals the regulatory role of lncRNA in the mechanism of pubertal estrus initiation - Xuan, Rong; Peng, Yanan; Wang, XinKun; Li, Wei; Huang, QiaoYan; Sun, HuiPing; Zhu, LeXiao; Gu, RuoHuai; Xing, Feng (Frontiers in Veterinary Science, 2025)
IntroductionPubertal estrus in sheep is crucial for reproductive maturation, with the hypothalamus playing a key role in its regulation. While long noncoding RNAs (lncRNAs) have gained attention for their involvement in the nervous system, their specific role in regulating pubertal estrus remains unclear.MethodsThis study performed transcriptome sequencing on hypothalamic tissues from Dolang sheep at pre-pubertal, pubertal, and post-pubertal stages. Identified lncRNAs were characterized based on genomic features, differential expression, potential cis-regulatory targets, and ceRNA relationships.ResultsA total of 1,589 lncRNAs were identified, including 848 known and 741 novel lncRNAs, with intergenic lncRNAs being most abundant. The majority of lncRNAs were 200–2000 nucleotides in length and contained 2–5 exons. A total of 129 differentially expressed lncRNAs were identified, with the highest differential expression between puberty and post-puberty. Cis-regulation analysis suggested that lncRNAs regulate genes involved in estrogen biosynthesis, dopamine transport, glycolipid metabolism, and nervous system development. LncRNAs may also impact reproductive hormone signaling, including the estrogen signaling pathway and gonadotropin-releasing hormone (GnRH) pathways, influencing growth, gonadal development, and sex hormone production. Specifically, ceRNA relationships such as LOC101105119–oar-miR-106b–GNAQ and LOC105607217–oar-miR-370-3p–PRKCA were validated.DiscussionOverall, this study demonstrates that lncRNAs regulate pubertal estrus initiation through ceRNA networks (e.g., LOC101105119–miR-106b–GNAQ) and hormone signaling, particularly the GnRH pathway, offering potential targets for sheep breeding.